Traditional Chinese Medicine Formula Kang Shuai Lao Pian Improves Obesity, Gut Dysbiosis, and Fecal Metabolic Disorders in High-Fat Diet-Fed Mice - Gong, Shuqing; Ye, Tingting; Wang, Meixia; Wang, Mengying; Li, Yufei; Ma, Lina; Yang, Yulian; Wang, Yi; Zhao, Xiaoping; Liu, Li; Yang, Min; Chen, Huan; et al. (Frontiers in Pharmacology, 2020)
High fat diet (HFD) induced obesity is a leading cause of metabolic disorders including cardiovascular diseases, diabetes, and aging etc. Accumulating evidences support the assumption of mitigating obesity through regulating gut microbiota as well as its metabolic status. Nevertheless, the inner-relationship between the obesity-related gut microbiota and the relevant metabolites are not well defined. In current study, we applied a traditional herbal formula Kang Shuai Lao Pian (KSLP) to HFD fed mice and evaluated its prevention effect against obesity. Special emphasis was addressed on analyzing the profiles of gut microbiota and fecal metabolites, for which 16S rRNA gene sequencing and non-target fecal metabolomics techniques were applied. We showed that KSLP could improve HFD induced obesity, glucose tolerance disorder, as well as gut dysbiosis. In the gut, KSLP corrected the increased abundance of Firmicutes and Proteobacteria, increased ratio of Firmicutes/Bacteroidetes and decreased abundance of Bacteroidetes caused by HFD. KSLP also reversed HFD-induced significant changes in the abundance of certain genus including Intestinimonas, Oscillibacter, Christensenellaceae_R-7_group, Ruminococcaceae_UCG-010 and Aliihoeflea. Pearson correlation analysis indicated that except for Ruminococcaceae_UCG-010, other 4 genera had positive correlations with obesity. In addition, 22 key fecal metabolites involving in amino acid-, dipeptide-, and lipid-metabolism etc. showed intimately relationship with KSLP effective genera of Intestinimonas, Oscillibacter and Christensenellaceae_R-7_group. Our results indicate that KSLP is a promising Traditional Chinese medicine (TCM) applicable for individuals with high fat diet habit. Linking of obesity phenotypes with gut microbiota as well as fecal metabolites is therefore a powerful research strategy to reveal the mechanism of obesity and the targets of intervention.